2014
DOI: 10.1074/jbc.m114.564070
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 2-mediated Phosphatidylinositol 3-kinase Signaling Selectively Inhibits Glycogen Synthase Kinase 3β to Regulate Aerobic Glycolysis

Abstract: Background: Insulin receptor substrate 2 (Irs-2)-mediated signaling by the insulin and insulin-like growth factor 1 receptors regulates metabolism. Results: Direct activation of PI3K by Irs-2 inhibits glycogen synthase kinase 3␤ (Gsk-3␤) to stimulate glucose uptake and aerobic glycolysis. Conclusion: Irs-1 and Irs-2 regulate distinct subsets of Akt effectors. Significance: The Irs-2-mediated PI3K signaling pathway could be targeted to inhibit tumor metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…Label-free mass spectrometric analysis of these immunocomplexes identified 20 proteins that were enriched upon PI3Kbi treatment (Supplementary Table S2). Among these, only the adaptor protein insulin receptor substrate 2 (IRS2) that mediates the activation of signaling pathways in response to ligand stimulation of cell surface receptors is reported to be Tyr-phosphorylated and harbors 6 YXXM motifs, therefore being a potent activator of PI3K (16,19). Subsequent, direct coimmunoprecipitation assays confirmed that PI3Kb inhibition induced a robust p85/IRS2 interaction (Fig.…”
Section: /Brafmentioning
confidence: 86%
“…Label-free mass spectrometric analysis of these immunocomplexes identified 20 proteins that were enriched upon PI3Kbi treatment (Supplementary Table S2). Among these, only the adaptor protein insulin receptor substrate 2 (IRS2) that mediates the activation of signaling pathways in response to ligand stimulation of cell surface receptors is reported to be Tyr-phosphorylated and harbors 6 YXXM motifs, therefore being a potent activator of PI3K (16,19). Subsequent, direct coimmunoprecipitation assays confirmed that PI3Kb inhibition induced a robust p85/IRS2 interaction (Fig.…”
Section: /Brafmentioning
confidence: 86%
“…SUM-159 cells were a gift from Arthur Mercurio (University of Massachusetts Medical School) and were grown in F12 media (Gibco) containing 5% FBS (MilliporeSigma), 5 μg/ml insulin (MilliporeSigma), and 1 μg/ml hydrocortisone (MilliporeSigma). Mammary tumor cells were isolated from female FVB MMTV-PyMT:Irs1 fl/fl ,Irs2 fl/fl mice, and PyMT:Irs1 -/-,Irs2 -/-cells were generated by infection with adenoviral Cre recombinase as described previously (19). PyMT mouse mammary tumor cells were grown in low-glucose (1 g/l) DMEM (Corning) containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cell functions that are regulated by IRS2 include glucose uptake, migration, and invasion (16). We initially investigated the effect of IRS2 mutations on invasion because PILC tumors have a high incidence of lymphovascular invasion and lymph node metastasis (1) -/-mouse mammary tumor cells ( Figure 4G) (19). Both of these cell lines are dependent upon IRS2 for invasion and their lack of IRS2 expression permits analysis of the IRS2 mutations without a background of endogenous expression.…”
Section: Identification Of Recurrently Mutated Genes In Pilc Pilc Tumentioning
confidence: 99%
“…Taxol, a taxane drug commonly used in cancer treatment, stabilizes microtubules, whereas nocodazole causes depolymerization of the tubulin cytoskeleton (23)(24)(25). IRS signaling was measured by assessing the phosphorylation status of AKT, a downstream signaling effector of PI3K, because the IRS proteins are required for the recruitment and activation of PI3K by the IGF-1R (4,5,26). Although microtubule stabilization by Taxol treatment did not alter the level of AKT activation (Fig.…”
Section: Igf-1r Signaling Is Dependent On the Microtubule Cytoskeletonmentioning
confidence: 99%
“…Notably, the IRS proteins are required for the activation of PI3K downstream of the IR and IGF-1R, which activate AKT and mechanistic target of rapamycin (mTOR) to promote proliferation, survival, motility, protein synthesis, and glucose metabolism (2)(3)(4)(5). IRS-1 and IRS-2 are expressed ubiquitously in humans, including in the normal and malignant mammary epithelium (1).…”
mentioning
confidence: 99%